OPA1 Regulates the Effects of Mitochondrial Dynamics Progress of Research on Different Cells of the Heart against Cardiomyopathy - Dongyang LI; Xinyve Zhang; Wang Qin; Yanwei Du (Journal of Cardiology and Cardiovascular Medicine, 2025)
Cardiomyopathies are critical clinical conditions. Their onset is associated with genetic factors, environmental impacts, and cellular dysfunctions. As a heterogeneous group of complex heart diseases, cardiomyopathies have been a central focus of medical research for a long time. With the advancement of science and technology and the deepening of research, an increasing number of genes and molecules have been demonstrated to be closely linked to the development and progression of cardiomyopathies. OPA1, a protein involved in the fusion of the inner mitochondrial membrane, plays a pivotal role in maintaining the normal function and morphology of mitochondria. In recent years, the significance of mitochondrial dynamics in cardiac health and disease has drawn considerable attention. Mitochondrial dysfunction is a major factor contributing to cardiac impairment. When the mitochondrial dynamics within cardiomyocytes are disrupted, it results in abnormal function and morphology of these cells. Overexpression of OPA1 significantly boosts the mitochondrial fusion activity in cardiomyocytes, enhances mitochondrial function, and alleviates oxidative stress-induced damage, thereby exerting a protective effect in the context of cardiomyopathy. Conversely, a deficiency of OPA1 leads to mitochondrial fragmentation and impaired energy metabolism, further deteriorating the function of cardiomyocytes. This article aims to delve into the mechanisms and effects by which OPA1 regulates mitochondrial dynamics to improve cardiomyopathy. It also summarizes the role of targeting OPA1 to regulate mitochondrial dynamics for the prevention and treatment of cardiomyopathy, with the intention of offering novel perspectives for the diagnosis and treatment of this condition.